DRC economy: The giant awakens - Franck Kuwonu (Africa Renewal, 2016)
Most news headlines from the Democratic Republic of the Congo (DRC) have one thing in common—their focus on conflict, particularly in the eastern part of the country. True, conflict is not new in the DRC, which has seen outbreaks in one form or another over the past three decades.